Surgical and Neurological Outcomes in Robotic Thymectomy for Myasthenic Patients with Thymoma - Khrystyna Kuzmych; Dania Nachira; Amelia Evoli; Raffaele Iorio; Carolina Sassorossi; Maria Teresa Congedo; Gregorio Spagni; Alessia Senatore; Giuseppe Calabrese; Stefano Margaritora; Elisa Meacci (Life)
Background: While the safety and feasibility of robotic thymectomy have been well documented through several studies, the surgical and long-term neurological outcomes in patients with thymomatous myasthenia gravis (MG), particularly in advanced stages, remain scarce. This study aims to evaluate the surgical outcomes in patients undergoing robotic-assisted thymectomy (RATS) for thymoma and to analyze neurological outcomes in patients with myasthenia. Material and Methods: Out of 128 robotic thymectomies performed at our institution between October 2013 and January 2022, clinical and pathological data from 55 patients diagnosed with thymoma were reviewed. Of these, thirty (54.5%) patients had concomitant acetylcholine-receptor-antibody-associated MG. Neurological outcomes were assessed using the Myasthenia Gravis Foundation of America post-intervention score (MGFA-PIS). Results: Thirty-nine (70.9%) procedures were performed using the left-sided approach. The mean operative time was 196.9 ± 79.9 min in patients with MG compared to 175.8 ± 61.6 min in non-MG patients (p = 0.285). Additionally, patients with MG had a longer in-hospital stay (4.8 ± 2.6 vs. 3.3 ± 2.2 days, p = 0.01) and a significantly higher need for intensive care unit admission (p < 0.01). No deaths were reported. The rates of conversions (3.3% vs. 4.0%, p = 0.895) and complications (p = 0.813) were comparable between the myasthenic and non-myasthenic thymomas. A multivariable analysis identified lung involvement (p = 0.023), vascular involvement (p = 0.04), and extended resection (p = 0.019) as significant risk factors for conversion and complications. The mean age of surgery for patients with MG was 54.5 ± 15.9 years. After a mean follow-up period of 35.6 ± 25.7 months, 18 (60%) patients with myasthenia showed clinical improvement of their condition. Specifically, 2 patients (6.6%) achieved complete stable remission (CSR), 2 (6.6%) experienced pharmacological remission (PR), 12 (40.0%) demonstrated minimal manifestation (MM), and 4 (13.3%) exhibited a combination of PR and MM. Twelve patients (40%) exhibited no changes, maintaining a stable clinical condition. No clinical worsening was observed. The overall improvement rates at 2 years and 5 years were 38% and 83%, respectively. Conclusions: RATS thymectomy is a safe and feasible approach for patients with thymoma. Patients with coexisting MG may benefit through a good rate of neurological improvement.